2012
DOI: 10.1103/physreve.85.021807
|View full text |Cite
|
Sign up to set email alerts
|

Pressure-induced structural change of intermediate-range order in poly(4-methyl-1-pentene) melt

Abstract: High-pressure in situ x-ray diffraction and specific-volume measurements on isotactic poly(4-methyl-1-pentene) melt have uncovered abrupt changes in the pressure dependence of microscopic structure as well as that of macroscopic density. The first sharp diffraction peak of the polymer melt, which is related to the intermediate-range order and is explained as resulting from the correlations between main chains, is suppressed at pressures less than 1 kbar. These changes in intermediate-range order show similarit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 68 publications
0
11
0
Order By: Relevance
“…The so-called polymerization (or van der Waals) peak represents real space distances consistent with the expected inter-backbone distances16 and so is the analogous feature of the FSDP peak. Hence, hereafter we will refer to this as FSDP for either network or polymer glasses.…”
mentioning
confidence: 91%
“…The so-called polymerization (or van der Waals) peak represents real space distances consistent with the expected inter-backbone distances16 and so is the analogous feature of the FSDP peak. Hence, hereafter we will refer to this as FSDP for either network or polymer glasses.…”
mentioning
confidence: 91%
“…In their x-ray diffraction study of pressure-induced structural changes of intermediate-range order in poly(4-methyl-1-pentene) (P4MP1) melts, Chiba et al [9] found that the first sharp diffraction peak (FSDP) intensity I(FSDP) decreased with pressure. Additionally, the ratio of I (FSDP) to the intensity of the second peak also decreased sharply under pressure.…”
Section: A Polymeric Model For the Ax 4 Molecular Solids Under Pressurementioning
confidence: 99%
“…Thus, a decrease in I(FSDP) points a disordering of these backbone-backbone correlations and a shift to higher momentum transfers. This led Chiba et al [9] to construct a model of polymer chains such that the polymer backbones were separated by void spaces filled with the polymer side chains. At low pressures, the void space between the backbone chains is quite large and consequently the resulting loose structure is highly compressible.…”
Section: A Polymeric Model For the Ax 4 Molecular Solids Under Pressurementioning
confidence: 99%
“…Combination of in situ synchrotron X-ray absorption techniques and molecular dynamics simulations were used to determine the density range of primitive lunar melts at pressures equivalent to those in the lunar interior (4.5 GPa and 1800 K) (Van Kan Parker et al, 2012): these extreme conditions were generated with tiny samples heated thanks to high electric current while squashing them in a press (figure 6); knowing the attenuation of the synchrotron X-ray beam through both the solid and molten parts of the sample, the density at high pressure and high temperature could be measured. High pressure in situ X-ray diffraction and specific volume measurements on isotactic poly(4-methyl-1-pentene) melt have uncovered abrupt changes in the pressure dependence of microscopic structure as well as that of macroscopic density (Chiba et al, 2012). It was proved another time that pressure has an essential role in the production and control of superconductivity (Sun et al, 2012): it is reported that in the superconducting iron chalcogenides, a second superconducting phase suddenly re-emerges at a critical temperature Tc reaching 48.0 K and above 11.5 GPa, after the Tc drops from the first maximum of 32 K at 1 GPa.…”
Section: Why Using Large Scale Facilities In Extreme Crystallography?mentioning
confidence: 99%